Goat’s Milk Powder Enriched with Red (Lycium barbarum L.) and Black (Lycium ruthenicum Murray) Goji Berry Extracts: Chemical Characterization, Antioxidant Properties, and Prebiotic Activity - Danijel D. Milinčić; Aleksandar Ž. Kostić; Steva Lević; Uroš M. Gašić; Dragana D. Božić; Relja Suručić; Tijana D. Ilić; Viktor A. Nedović; Bojana B. Vidović; Mirjana B. Pešić (Foods)
The current trend in food innovations includes developing products containing plant ingredients or extracts rich in bioactive compounds. This study aimed to prepare and characterize skimmed thermally treated goat’s milk powders enriched with lyophilized fruit extracts of Lycium ruthenicum Murray (GMLR) and Lycium barbarum L. (GMLB). Proximate analysis, ultra-high performance liquid chromatography with quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF-MS), Fourier transform infrared spectroscopy using attenuated total reflection (FTIR-ATR), and electrophoretic analysis were assessed. Total phenolic content (TPC), total protein content, and antioxidant properties of enriched goat milk powders were determined spectrophotometrically, and prebiotic potential was evaluated by the broth microdilution method. A total of 25 phenolic compounds and 18 phenylamides were detected in the enriched goat milk powders. Electrophoretic analysis showed the absence of proteolysis in the prepared powders. The GMLR showed the highest TPC and displayed a ferric ion-reducing power, probably contributed by anthocyanins and some phenylamides. GMLR and GMLB had higher ABTS radical scavenging activity but lower ferrous ion-chelating capacity than control goat′s milk powder. GMLB and GMLR in a dose-dependent manner (0.3–5 mg/mL) showed a growth-promoting effect on probiotic strains. In summary, prepared goji/goat milk powders, primarily GMLR, might be used as prebiotic supplements or functional food additives.